Analisa Kegagalan Tubing Hidraulik untuk Instrumen - Nadya Laurenza; Arie Wibowo; Husaini Ardy (Jurnal Metalurgi dan Material Indonesia, 2019)
Hydraulics tubing austenitic stainless steel 316L for offshore instrument was failed due to pitting corrosions attack. This research aims to determine the root causes of tube leakage by visual examination of new and failed tube, scanning electron microscope (SEM) examination, deposits analysis by energy dispersive spectroscope (EDS), and microstructural analysis by light microscope. The examination results show that pitting corrosions were originated from surface defects as residences for deposit and marine growth. Pitting corrosions form a tunneling underneath the surface which one of the characteristic of sulpfhur reduced bacteria (SRB) corrosion. This conclusion is also supported by high sulphur concentration in surface deposit as a results of bacteria metabolisms and formation of FeS compound. Crevice corrosion also contributed to pitting formation because critical crevice temperature of 316L tubing material is around 10oC, lower than the service environment temperature. These two corrosion modes may occur separately or combined. Surface defects might be originated from improper handling, storage, or during construction, which induce scratches on tubing surface. To prevent pitting corrosion reoccurence, it is recommended to use fire retardant polyurethane thermoplastic rubber sheathing stainless steel 316L tube or superduplex stainless steel tube material which critical crevice temperature is 35˚C.